UTILIZATION OF PRE- AND POST-COMPARATIVE ANALYSIS OF INTRA-LESIONAL DEXAMETHASONE COMBINED WITH HYALURONIDASE IN THE TREATMENT OF PATIENTS WITH ORAL SUBMUCOUS FIBROSIS: A CROSS-SECTIONAL STUDY - Kumar, Rahul; Md Nayeemuddin; Kumar, Ashutosh (Student’s Journal of Health Research Africa, 2024)
Background Oral Submucous Fibrosis (OSMF) is a chronic and potentially malignant disorder characterized by collagen deposition in the oral mucosa, primarily affecting the South Asian population. Despite its high prevalence and association with oral cancer, the pathophysiology of OSMF remains poorly understood, complicating effective treatment options. Aim To examine the efficacy of intra-lesional corticosteroid injections in alleviating symptoms and improving oral functionality in patients diagnosed with OSMF. Methods This clinic-observational study included patients diagnosed with OSMF. A total of 120 participants, aged 18 to 50 years, were administered intra-lesional injections of dexamethasone and hyaluronidase twice weekly for eight weeks. Clinical assessments, including mouth opening and burning sensation measured on a Visual Analogue Scale (VAS), were conducted tri-monthly. Statistical analysis was performed using SPSS to evaluate treatment efficacy. Results The study included 120 patients with OSMF, 68% (N = 82) were male, and 32% (N = 38) were female. The study revealed a significant improvement in mouth opening from 23.75 ± 2.54 mm pre-treatment to 27.50 ± 3.15 mm post-treatment (p = 0.001). Additionally, the VAS score for burning sensation decreased from 5.80 ± 1.30 to 2.90 ± 1.95 (p = 0.001), indicating effective symptom relief. These findings suggest that intra-lesional corticosteroid therapy significantly enhances oral mobility and reduces discomfort in patients with OSMF. Conclusion Intra-lesional corticosteroid therapy is an effective treatment for improving mouth opening and alleviating burning sensations in patients with OSMF. These results underscore the potential of corticosteroids in managing this precancerous condition and improving patients’ quality of life. Recommendations The study recommends incorporating intra-lesional corticosteroid therapy as a primary treatment for OSMF due to its effectiveness in improving oral mobility and reducing discomfort. Additionally, further research is suggested to explore long-term outcomes and the benefits of combining this therapy with other treatment modalities.